Publishing journal articles - Becker, Lucinda M. 1963-; Denicolo, Pam. (Los Angeles, Calif London SAGE, 2012)
Practical, no-nonsense, accessible guide to planning, writing and publishing a journal article.
When, what and where to publish -- Selecting your topic/adapting your work -- Planning and getting started -- Coping with writer's block -- Getting the style right -- Learning how to stop writing your article -- Working with editors and reviewers -- Recovering from rejection -- Intellectual property rights.
Includes bibliographical references (p. [139]) and index.
Keywords: Academic writing -- Publishing; Academic writing; English language -- Rhetoric; Technical writing; Authorship -- Marketing